Deformation and Stability Analysis of Surrounding Rock Mass in Deep Underground Cavern Based on Microseismic monitoring and Numerical Modelling. Issue 7 (October 2021) - Huang, Xiao; Xiao, Peiwei; Xu, Nuwen; Dong, Linlu; Mao, Haoyu; Zhu, Zhongping; Zhao, Tieshuan
Abstract: In the excavation and unloading process of large-scale underground engineering, surrounding rock mass damages such as splitting, rock burst and collapse will often occur, affecting the progress and safety of the project. Correctly identifying and delineating the potential instability and failure area of surrounding rock mass and forecasting in advance can effectively reduce the hidden dangers of engineering safety. In this paper, a comprehensive analysis method combining microseismic (MS) monitoring and numerical simulation is proposed to analyse the effect of structure planes on the stability of surrounding rock mass of underground cavern and predict the deformation. First, numerical simulation is applied to analyse and predict the deformation and stress evolution characteristics of surrounding rock mass. Second, based on the MS monitoring data of the underground powerhouse and field investigation, the temporal and spatial distribution characteristics of MS activity were analysed, and the failure region was revealed and delineated. Finally, the effectiveness of the proposed method is verified by the comparison of MS monitoring results and numerical simulation. The results show that MS events are obviously concentrated in the surrounding rock mass damage area. The failure of spalling and rock-burst in underground powerhouse area is the typical brittle failure under high in-situ stress and low strength-to-stress ratio. In essence, the collapse at the top arch of auxiliary powerhouse is caused by the combined action of high in-situ stress and unfavourable structural plane. The results of MS monitoring and numerical simulation have a good corresponding relationship, and the conclusions provide technical guidance for subsequent construction schemes and support measures.